2006
DOI: 10.1210/me.2005-0473
|View full text |Cite
|
Sign up to set email alerts
|

Socs2 and Elf5 Mediate Prolactin-Induced Mammary Gland Development

Abstract: The proliferative phase of mammary alveolar morphogenesis is initiated during early pregnancy by rising levels of serum prolactin and progesterone, establishing a program of gene expression that is ultimately responsible for the development of the lobuloalveoli and the onset of lactation. To explore this largely unknown genetic program, we constructed transcript profiles derived from transplanted mammary glands formed by recombination of prolactin receptor (Prlr) knockout or wild-type mammary epithelium with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
118
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 37 publications
8
118
0
Order By: Relevance
“…Evidence is mounting that members of the SOCS family are essential in controlling the onset, extent, and duration of cytokine-induced Stat3 and Stat5 signaling. While Socs1 (Lindeman et al, 2001) and Socs2 (Harris et al, 2006) modulate prolactin signaling during pregnancy, Socs3 is essential for the functional development of mammary tissue during pregnancy and for the timely execution of mammary tissue remodeling during involution, as shown in this study.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Evidence is mounting that members of the SOCS family are essential in controlling the onset, extent, and duration of cytokine-induced Stat3 and Stat5 signaling. While Socs1 (Lindeman et al, 2001) and Socs2 (Harris et al, 2006) modulate prolactin signaling during pregnancy, Socs3 is essential for the functional development of mammary tissue during pregnancy and for the timely execution of mammary tissue remodeling during involution, as shown in this study.…”
Section: Discussionmentioning
confidence: 53%
“…In mammary tissue, Socs1 negatively regulates prolactin signaling and deletion of the respective gene results in precocious mammary development and a rescue of prolactin receptor (PrlR) haploinsuffiency (Lindeman et al, 2001). The inability of PrlR-hemizygous mice to form a functional alveolar compartment and lactate was also rescued by the deletion of both Socs2 alleles (Harris et al, 2006). In both instances, this functional rescue was paralleled by the activation of Stat5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel study, an increase in Socs2 transcripts was observed in SCp2 mammary epithelial cells treated with a lactogenic stimulus. 18 Within the mammary gland, we have demonstrated that Socs2 has an important role in regulating PRL signal transduction during pregnancy and lactation. Although Socs2 was not essential for mammopoiesis and lactogenesis, removal of both Socs2 alleles in mice was sufficient to restore lactation in PRLR heterozygous females.…”
Section: Introductionmentioning
confidence: 98%
“…Transcript profiling studies to determine gene signatures associated with alveolar proliferation and differentiation have identified Socs2 as a PRL target gene. 18 In this study, transcript profiling was performed on outgrowths from day 6 and 8 pregnant recipients; these outgrowths were derived from explants of PRLR -/-or PRLR +/+ mammary epithelium grown in de-epithelialised fat-pads of wild-type mice. Socs2 was one of 239 epithelial-specific transcripts found to be down-regulated in the PRLR -/-transplants.…”
Section: Introductionmentioning
confidence: 99%